Structural elucidation and hypoglycemic effect of an inulin-type fructan extracted from Stevia rebaudiana roots. Issue 5 (23rd February 2023) - Tang, Zhiyan; Shao, Taili; Gao, Lan; Yuan, Pingchuan; Ren, Zhengrui; Tian, Lei; Liu, Wei; Liu, Chunyan; Xu, Xiuxian; Zhou, Xuan; Han, Jun; Wang, Guodong
Abstract : A novel fructan (SRRP) from S. rebaudiana roots ameliorates glucose and lipid metabolism disorders in type 2 diabetic mice via gut microbiota regulation. Abstract : Diabetes mellitus (DM) is a common chronic medical condition characterized by hyperglycemia resulting from abnormal insulin functionality, of which type 2 DM (T2DM) is the predominant form. An inulin-type fructan, denoted as SRRP, was obtained from Stevia rebaudiana roots via hot-water extraction and alcoholic precipitation, which was subsequently purified by column chromatography. The extracted SRRP sample had a molecular weight of 5.4 × 10 3 Da. Structural analyses indicated that SRRP was composed of 2, 1-linked-β-d -fructofuranosyl and α-d -glucopyranosyl residues in a ratio of approximately 29 : 1. In vivo assays revealed that SRRP significantly reduced fasting blood glucose levels, improved insulin resistance, decreased oxidative stress, and regulated lipid metabolism in T2DM mouse models. In addition, SRRP altered the diversity of the gut microbiota and its metabolites in T2DM mice; it increased probiotic bacteria and the concentration of short-chain fatty acids and decreased harmful bacteria. The findings demonstrate the potential of SRRP in the treatment of T2DM.